Clothing Sustainability and Upcycling in Ghana. (2nd September 2019) - James, Alberta St. John; Kent, Anthony
Abstract: The aim of this paper is to assess opportunities for the upcycling of waste clothing through design workshops held in Accra, Ghana. An upcycling approach to clothing longevity examines how garments can be re-designed and resold in a new form. Significant amounts of surplus and second-hand clothing from the developed world and large producer nations, for example China, are distributed to Africa and sold in local markets at affordable prices. The research was conducted into upcycling waste clothing from the market by five groups of fashion design students at Accra Technical University (ATU). A participatory research design was applied to the project and the initial briefing to design groups confirmed the concept of upcycling and the design parameters. Each group defined a design theme, made a selection of clothes and accessories in the Accra market and returned to the university to conceptualise and re-create clothes and accessories. The project culminated in presentations of finished garments modelled by the students. It addressed the disposal stage of the circular economy model of clothing sustainability by providing new knowledge of how waste clothing, readily available in a developing country's market can be sourced and creatively re-designed into new garments and accessories.